1995
DOI: 10.1523/jneurosci.15-05-03970.1995
|View full text |Cite
|
Sign up to set email alerts
|

Molecular, functional, and pharmacological characterization of the metabotropic glutamate receptor type 5 splice variants: comparison with mGluR1

Abstract: This work was wppwted by grants from the CNRS, CEE (B102-CT93-0243), DRET (9 l/161) the Human Frontier5 Science Projiram (RG 5792B), and Bayer Company (Germany). This work has been d&e as part of the Bi oAveni n program supported by Rhone-Poul enc with the participation of the French Ministrv of Research and the French Ministrv of Industrv. J.G. was i supported by an IPSEN and then a Spnni\h governmen; fellowship\. We thank Dra. L. Journot and B. Chin! for critical reading of the manuscript, Dr. M. Lafon-Canal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
190
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 258 publications
(201 citation statements)
references
References 41 publications
11
190
0
Order By: Relevance
“…Although the mGlu5-truncated receptor displayed constitutive activity, no such activity could be detected with GABA B2 . This was in agreement with the higher constitutive activity measured with mGlu5 compared with GABA B receptor (51,52). However, in both cases, these HDs were activated by positive allosteric regulators CGP7930 and DFB for GABA B2 and mGlu5 HDs, respectively.…”
Section: Discussionsupporting
confidence: 88%
“…Although the mGlu5-truncated receptor displayed constitutive activity, no such activity could be detected with GABA B2 . This was in agreement with the higher constitutive activity measured with mGlu5 compared with GABA B receptor (51,52). However, in both cases, these HDs were activated by positive allosteric regulators CGP7930 and DFB for GABA B2 and mGlu5 HDs, respectively.…”
Section: Discussionsupporting
confidence: 88%
“…Because the VFTM of class-C GPCRs has been proposed to reach the closed (active) form in the absence of agonists, we were wondering whether this could be at the origin of constitutive activity of these receptors. When expressed in heterologous cells, both group-I mGluRs (mGlu1 and 5) display constitutive activity, as shown by the high basal IP formation measured in cells expressing these receptors compared to mock-transfected cells (Joly et al, 1995;Prézeau et al, 1996). However, such a constitutive activity was not inhibited by competitive antagonists that prevent the closure of the VFTM (Prézeau et al, 1996).…”
Section: The Heptahelical Domain Of Group-i Mglurs Displays Constitutmentioning
confidence: 99%
“…Group II (mGluRs 2 and 3) and group III (mGluRs 4 -8) receptors inhibit adenylyl cyclase, although with different pharmacological profiles (for review, see Pin and Duvosin, 1995;Roberts, 1995). Ligand-binding studies have shown the striatum to possess a high density of mGluR binding sites (Albin et al, 1992), and several mGluR mRNAs and proteins are expressed by striatal neurons, including members of all three mGluR groups (Abe et al, 1992;Martin et al, 1992;Shigemoto et al, 1992Shigemoto et al, , 1993Fotuhi et al, 1993;Ohishi et al, 1993a,b;Saugstead et al, 1994;Testa et al, 1994;Joly et al, 1995;Romano et al, 1995).…”
Section: Abstract: Metabotropic Glutamate Receptor; Basal Ganglia; Smentioning
confidence: 99%